Migraine Awareness in Italy and the Myth of "Cervical Arthrosis". Issue 1 (26th September 2019) - Rota, Eugenia; Zucco, Riccardo; Guerzoni, Simona; Cainazzo, Maria M.; Pini, Luigi A.; Catarci, Teresa; Granella, Franco
Abstract : Objective: The primary aim of this study was to assess the degree of awareness migraine patients had of their condition. The secondary aims were to evaluate the frequency of an incorrect diagnosis of "cervical arthrosis" in patients unaware of having migraine and to compare the clinical features, diagnostic investigation, and treatment strategies between the 2 subgroups of migraineurs, that is, those with and without the incorrect diagnosis of "cervical arthrosis." Methods: Patients, between 18 and 65 years, were consecutively referred to 5 Headache Centers in 2 Italian regions for a first visit. They fulfilled the diagnostic criteria for migraine (with/without aura, episodic/chronic) and were enrolled in this cross‐sectional study. Each patient underwent a specific cranial/cervical musculoskeletal clinical examination. Results: A total of 117/250 subjects (46.8%) were unaware that they suffered from migraine. In these unaware subjects, the most frequently reported diagnosis was "cervical arthrosis" in 34/117 (29.1%), followed by tension‐type headache in 23/117 (19%). The cervical region was the most common site of pain onset in the so‐called "cervical arthrosis" group (52.9%, P < .0001), where also more pericranial (58.8%; P = .041) and neck (70.6%; P = .009) muscle tenderness, restricted range of cervical vertical (47.1%; P < .001), and lateral (29.4%; P = .040) movements were reported. More "cervical arthrosis patients" had been referred to an Emergency Department (88.2%; P = .011) and had undergone more cervical spine radiography (23.5%; P = .003) and magnetic resonance imaging (20.6%; P = .044). While they had used fewer triptans (11.8%; P = .007) and received less pharmacological prophylaxis (2.9%; P = .004). Conclusions: In our sample, there were high misdiagnosis rates for migraine sufferers in Italy. The most common misdiagnosis, that is, "cervical arthrosis, " led to misuse of healthcare facilities and had a negative impact on the migraine treatment.